Yielding and lateral torsional buckling limit states for butterfly-shaped shear links. (1st February 2019) - Farzampour, Alireza; Eatherton, Matthew R.
Highlights: Equation for lateral torsional buckling of butterfly-shaped shear links is derived. Shear strength associated with flexural and shear yielding are derived. Finite element models results corroborate the derived equations. Abstract: A promising type of hysteretic damper used for seismic energy dissipation consists of a steel plate with cutouts leaving butterfly-shaped links that undergo flexural yielding when the plate is subjected to shear deformations. Butterfly-shaped links, which have linearly varying width between larger ends and a smaller middle section, have been shown in previous research to possess substantial ductility and stable energy dissipation capability, but can be prone to other limit states such as lateral torsional buckling (LTB) or shear yielding. The current work examines the three potential limit states of LTB, flexural yielding and shear yielding, and develops methods to predict which limit state will control along with the associated strength. First, the governing differential equation for elastic LTB of a butterfly-shaped link is formulated and a relatively simple equation is developed to predict the critical shear force associated with elastic LTB. The shear yielding and flexural yielding limit states are then described and equations are presented to predict the associated shear strength of the butterfly-shaped links. The accuracy of the equations is then evaluated against a series of finite element (FE) models that are validated against previous experiments. It was found that butterfly-shaped links that are thick enough to prevent lateral torsional buckling, experience a progression of limit states including: (1) yielding in one mode (flexural or shear), (2) geometric hardening associated with increasing tension forces in the links, and (3) further yielding associated with biaxial stresses. The equation developed for lateral torsional buckling produced an average LTB strength that was within 4% of the FE model results and the equations for flexural yielding and shear yielding predicted the strength of the FE models within 3% on average.